Phonetic Analysis of English Segmental Sounds Produced by The English Young Learners' Teachers - Azizah, Nadya Nur; Musthafa, Bachrudin (ENGLISH FRANCA : Academic Journal of English Language and Education, 2024)
Indonesian English learners undoubtedly encounter difficulties in articulating the authentic phonetic sounds of English. This occurs because specific English phonemes are absent in the learner's native language, leading to unnatural pronunciation. Consequently, the teacher's role is crucial in developing proficient language skills, particularly in pronunciation, among English language learners. Teachers' proficiency in English is expected to help students correct their errors. Researchers are presently analyzing the pronunciation skills of English teachers. This study employs descriptive method and two data collection instruments: interview and picture description task. This study aimed to identify specific sounds that are frequently unnatural in English segmental and to determine the factors contributing to the unnatural sounds produced by EYL teachers. The findings of this study showed; an in-depth phonetic analysis of the teachers' production in terms of place of articulation, manner of articulation as well as distinctive features for the production of English consonant sounds, and openness of the mouth, tongue elevation, position of tongue elevation, lips shapes, as well as length of vocalization for the production of English vowel sounds. This study also determined that mother tongue interference as the primary factor of the unnatural sound made by the teachers.